Menganalisis Waktu Tunggu Pelayanan Rawat Jalan dengan Kepuasan Pasien di Rumah Sakit Santa Elisabeth Medan - Pomarida Simbolon; Illene Annica Sarid Sarumaha (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Outpatient registration time service in a hospital is a phenomenon that refers to the actions or activities of a system within a hospital or health care facility that aims to maintain and improve health, prevent and treat diseases, and restore health. Patient waiting time in the outpatient registration section is a cause of patient dissatisfaction with the service. If the waiting time for service is long, it will reduce patient comfort and vice versa. The aim is to determine the relationship between outpatient registration service time and patient satisfaction at Santa Elisabeth Hospital Medan in November 2025. This type of analytical research uses a cross-sectional design. The research sample was 95 respondents with an accidental sampling technique. The instruments used were a patient satisfaction questionnaire and an observation sheet for registration service time. Data analysis used the Chi-square test. The results of this study obtained a patient satisfaction level of 82 people (86.3) and a fast outpatient registration service time of 51 people (53.6). The results of the Chi-Square statistical test obtained a p-value of 0.008 (p<0.05) indicating a relationship between outpatient registration service time and patient satisfaction at Santa Elisabeth Hospital Medan in November 2025. It is hoped that Santa Elisabeth Hospital Medan must continue to maintain good and friendly service times and increase outpatient service times for patients efficiently.